2013
DOI: 10.1136/bmjopen-2013-002976
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health knowledge, attitude and practice/behaviour in an urbanising community of Nepal: a population-based cross-sectional study from Jhaukhel-Duwakot Health Demographic Surveillance Site

Abstract: ObjectivesThis study determined the knowledge, attitude and practice/behaviour of cardiovascular health in residents of a semiurban community of Nepal.DesignTo increase the understanding of knowledge, attitude and practice/behaviour towards cardiovascular health, we conducted in-home interviews using a questionnaire based on the WHO STEPwise approach to surveillance and other resources, scoring all responses. We also recorded blood pressure and took anthropometric measurements.SettingOur study was conducted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
113
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 43 publications
(43 reference statements)
31
113
14
2
Order By: Relevance
“…Similar findings were reported in studies conducted in two villages near Kathmandu (Nepal) [12] and in Karachi (Pakistan) [13] RESEARCH in relation to their attitude towards cardiovascular health [12] and modifiable risk factors for heart diseases. [13] In contrast, the level of knowledge and practice of cardiovascular health were statistically different according to age, [12] where participants ˂35 years old were more likely to have a greater adequate knowledge and better practice than those who were >45 years of age. [12,13] This was consistent with the results of other studies on knowledge of risk factors and prevention regarding diabetes in eastern Saudi Arabia, [14] and of chronic diseases in Jinan (China).…”
Section: Researchsupporting
confidence: 75%
See 3 more Smart Citations
“…Similar findings were reported in studies conducted in two villages near Kathmandu (Nepal) [12] and in Karachi (Pakistan) [13] RESEARCH in relation to their attitude towards cardiovascular health [12] and modifiable risk factors for heart diseases. [13] In contrast, the level of knowledge and practice of cardiovascular health were statistically different according to age, [12] where participants ˂35 years old were more likely to have a greater adequate knowledge and better practice than those who were >45 years of age. [12,13] This was consistent with the results of other studies on knowledge of risk factors and prevention regarding diabetes in eastern Saudi Arabia, [14] and of chronic diseases in Jinan (China).…”
Section: Researchsupporting
confidence: 75%
“…[13] In contrast, the level of knowledge and practice of cardiovascular health were statistically different according to age, [12] where participants ˂35 years old were more likely to have a greater adequate knowledge and better practice than those who were >45 years of age. [12,13] This was consistent with the results of other studies on knowledge of risk factors and prevention regarding diabetes in eastern Saudi Arabia, [14] and of chronic diseases in Jinan (China). [15] A cross-sectional study among black and Hispanic females in the USA found that younger-aged females (<55 years) were less conscious of heart disease being the leading cause of mortality in women and were less likely to state that they were very well or knowledgeable concerning heart disease compared with older-aged women.…”
Section: Researchmentioning
confidence: 66%
See 2 more Smart Citations
“…In a country like Nepal, where diabetes imposes a huge financial burden on patients [34], and where diabetes management is challenged by poor health literacy [35] and patients’ limited knowledge of diabetes [18,36], the extent to which self-monitoring should be promoted and to what extent the benefits of self-monitoring may be achieved (and how) should be carefully considered. It is also important to have a realistic expectation of how self-monitoring practices might be implemented effectively.…”
Section: Discussionmentioning
confidence: 99%